Effect of vibratory peening on wear behavior of Al2O3/SiCp reinforced Al2024 aircraft alloy - Er, Yusuf (Walter de Gruyter Gmbh, 2021)
Aluminum alloys and composites arc widely used in the field of aviation due to their high strength/weight ratio. However, due to their relatively low hardness values, they have poor wear resistance. In this study, a hybrid composite material was produced through stir casting method. Al2O3 and SiCp particles in 2.5, 5 and 7.5 wt.-% were added into Al2024 matrix material, which is widely used in the aviation industry, in order to increase the wear resistance of composites. The vibratory peening process was applied to the surfaces of the produced samples. The samples were then subjected to a reciprocating wear test. As a result of the tests, it was observed that the vibratory peening process has an important effect on the wear resistance of the samples.
Keywords: Stir casting; vibratory peening; wear; Al2024; hybrid composite